THE INFLUENCE OF USING SHORT STORY ANIMATION ON STUDENTS’ VOCABULARY MASTERY - Syahla Nurhaliza; Sutrisno Sadji Evenddy; Ledy Nurlely (Datokarama English Education Journal, 2023)
This research purpose was to determine the influence of short story narrative text on students’ vocabulary mastery at the 10th grade of SMAN 1 PETIR. This research was done by true-experimental with random sampling. The population of this research was all of the first-grade high school students in Banten province, consisting of 350 students. The researcher used two classes, X MIPA 4 as the experimental and X MIPA 5 as the control class. Both classes consisted of 35 students. In obtaining the data, the researcher used multiple-choice questions as instruments. Try out was conducted as the first step to get the data. After conducting the tryout, the researcher gave a pre-test in both classes. The researcher gave the treatment in the experimental class using Short Story Animation as a media, and in the control class, the discussion method used a module. The result of the calculation by Independent T-test found that (0,002 < 0,005), which means the hypothesis alternative (Ha) is accepted. The effectiveness of using Short Story Animation Narrative Text can be seen in the ability obtained after the treatment.